PENGARUH MALTODEKSTRIN TERHADAP SIFAT FISIK DAN KIMIA PEWARNA BUNGA TAPAK DARA (Catharanthus roseus) SEBAGAI BIOCOLOUR PANGAN - Reni Erfianti; Titi Mutiara Kiranawati; Ummi Rohajatien (BPFP Faperta UNIB, 2023)
Tapak dara flower (Catharanthus roseus) is an ornamental plant originating from Central Amerika. This natural pigment derived from the tapak dara flower is made in powder with maltodextrin as a drying agent. This experimental study uses a one-factor, Completely Randomized Design (CRD) research method with 3 levels of maltodextrin concentration, namely 20%, 30%, and 40%. The data obtained were analyzed statistically using the ANOVA test and continued with the DMRT as a posthoc test if there were significant differences. The results showed that adding maltodextrin with concentrations of 20%, 30%, and 40% and repeated twice had significant differences in water content, pH, level of sweetness (°brix), color, solubility, and total dissolved solids. The results of the chemical analysis of tapak dara corolla dye powder with a maltodextrin concentration of 40% had a water content, and the lowest pH was a water content of 4,90% and a pH value of 3,41. Maltodextrin concentration of 20% has the lowest sweetness level (°brix) of 5,35%. The results of the physical properties study showed that tapak dara corolla dye powder with 40% maltodextrin concentration had the lowest color brightness level (L*) of 32,91; the lowest reddish color level (a*) of 35,26 and yellowish color level (b*) the lowest is 35,26. The concentration of 20% maltodextrin has the lowest solubility and total dissolved solids, namely the solubility of 92,84% and the total dissolved solids of 5,35%. Adding maltodextrin with a concentration of 30% gave the best dye results based on water content, pH, level of sweetness (°brix), color, solubility, and total dissolved solids using the De Garmo method.